Intergenerational Social Tensions in the Workplace: Perspectives on the Role of Lecturers in Collaboration - Nabawi, Denny; Zunaidah; Hamira; Najib, Ahmad Khoirun; Ufaira, Rifda Alda (Graduate Program Magister Manajemen Pendidikan, 2025)
This study investigates intergenerational social tensions in the workplace, with a particular focus on how lecturers perceive and navigate these tensions to facilitate collaboration. It examines the influence of perceived control, intentionality, and external attributions in shaping internal attribution processes within an academic environment. A quantitative research approach was adopted utilizing an exploratory model. Data were collected from 118 lecturers in Palembang, Indonesia, through structured questionnaires. Structural Equation Modeling-Partial Least Squares (SEM-PLS) was employed to examine the relationships between variables, with a particular emphasis on attribution theory. External attribution plays a significant mediating role, suggesting that lecturers primarily interpret intergenerational tensions through external factors such as organizational policies and workplace culture before forming personal attributions. This study enhances the understanding of workplace dynamics by applying attribution theory to the context of intergenerational tensions in academia, which underscores the critical role of external attribution in shaping perceptions that influence internal attribution and also offers practical insights for developing inclusive management strategies in fostering effective collaboration across generations.